The Development of A Mobile-Based Area Recommendation System Using Grid-Based Area Skyline Query and Google Maps - Annisa; Alyssa, T. Sandra; Agmalaro, Muhammad Asyhar (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2024)
Choosing a location for a business or place of residence is an essential task in our daily lives. Typically, a location is considered favorable if it is in proximity to profitable facilities that enhance its value while being distant from facilities that diminish its value. However, conducting surveys in the field to identify desirable candidate locations is not always feasible. Factors such as high costs, inclement weather, and transportation limitations can hinder survey activities. This study aims to develop a mobile-based system for location selection using the Grid-based Area Skyline (GASKY) algorithm in conjunction with Google Maps. Google Maps is widely utilized for location-based decisions and is familiar to mobile application users. GASKY is employed for its capability to recommend locations based on user-provided information regarding desired facilities near the target location and facilities to be avoided, eliminating the need to input candidate locations from survey results. The outcomes of this study include a mobile-based application that utilizes the Google Maps API to create data collection modules. Mobile-based applications utilizing GASKY offer convenience, as they can be accessed by users anytime and anywhere.